Associations between fine particulate matter and its constituents and intrahepatic cholestasis of pregnancy - Cheng Li; Ying-Zhou Ge; Yan-Hui Hao; Jing-Jing Xu; Si-Wei Zhang; Si-Yue Chen; Hai-Dong Kan; Xia Meng; He-Feng Huang; Yan-Ting Wu (Ecotoxicology and Environmental Safety)
Few studies have reported an association between intrahepatic cholestasis of pregnancy (ICP) and preconception exposure to PM2.5 and sunlight duration, but there has been no in-depth analysis of the correlation between ICP and different constituents of PM2.5. Thus, we performed this retrospective analysis among 160,544 pregnant women who delivered between 2014 and 2020, to further estimate the impact of different constituents of PM2.5, as well as the duration of sunlight, on ICP via generalized linear models. During the three months prior to conception, the adjusted odds ratios (aORs) for ICP were 1.176 (95 % CI: 1.066, 1.298) for a 10 μg/m3 increase in PM2.5, 1.080 (95 % CI: 1.026, 1.138) for a 1 μg/m3 increase in sulfate (SO42–), 1.069 (95 % CI: 1.025, 1.115) for a 1 μg/m3 increase in organic matter (OM), 1.274 (95 % CI: 1.049, 1.546) for a 1 μg/m3 increase in black carbon (BC), and 1.213 (95 % CI: 1.088, 1.353) for a 1-hour decrease in sunlight duration. In addition, during the preconception period, increased exposure to PM2.5 constituents (including SO42–, OM, and BC) and decreased sunlight duration interactively associated with ICP. Moreover, exposure to OM during the first trimester (aOR=1.043, 95 % CI: 1.004, 1.083) and to BC during both the first trimester (aOR=1.201, 95 % CI: 1.000, 1.442) and the second trimester (aOR=1.278, 95 % CI: 1.048, 1.558) were found to elevate the risk of ICP. In the future, women preparing to conceive should increase sunlight exposure and avoid exposure to air pollution, and the constituents related to anthropogenic emissions should be controlled to prevent these associations.